Problemas Integradores. Vía Para La Activación Del Aprendizaje (Global Journal of Human-Social Science, 2022)
The objective of the paper is to offer problems based on the integration of contents that contribute to the activation of the teaching-learning process of students in the Chemistry-Physics discipline of the "Chemistry Education" career of the University of Camagüey. Theoretical research methods were used in order to systematize pedagogical theories that lead to a more active involvement of students in their learning process. Likewise, the results achieved from its implementation in the educational practice in the last three years are described, showing a qualitative and quantitative leap in the quality of learning.
Keywords: teaching; learning; content integration; activation of the teaching-learning process